Culturele grondslagen van de Monumentenwet (Bulletin KNOB, 2012)
In comparison with other European nations, the Netherlands was very late in introducing a Monuments and Historic Buildings Act. Not until 1961 did a definitive Act come into effect in order to protect ‘monuments of history and art’ in peace time against undesired decline and defacement. The cultural foundations for this were laid much earlier, particularly in the nineteenth century, simultaneously with the forming of nations and the rise of new journals, organisations and scientific disciplines. This article examines how the definition of the concept of monument in the first Section of the Act was founded on the preceding debates and interpreted afterwards.One of the three principal criteria is ‘beauty’. In relation to the concept of ‘art’ this has the advantage of appealing to both the classical Bildung values and the romantic fascination for ruins and visible traces of a distant past.Another criterion is the ‘significance for scholarship’. In this context the advocates of protection of monuments and historic buildings active around 1910 chiefly had the humanities in mind. Especially because of their irreplaceable historical materiality monuments and historic buildings are of importance as sources of knowledge on living, working, building and development of taste in the course of time. Recently, designation of scientific value is limited to objects or buildings specifically constructed for the exercise of (exact) sciences, such as a laboratory or radio telescope.The third criterion, ‘folkloric value’, relevant for e.g. bakehouses and other ‘small’ monuments, was cancelled when the old Act was replaced by the new one in 1988. Almost without being noticed it was substituted by the term ‘cultural-historical value’. This caused friction when assessing the ‘traces of the Second World War’: they are reminiscent of a culture of oppression and collaboration, not of civilization.In the most recent amendment the minimum age of fifty years as a criterion was abandoned, but for the moment the Euromast in Rotterdam is the youngest protected monument.